2014
DOI: 10.2147/ijn.s61273
|View full text |Cite
|
Sign up to set email alerts
|

In vivo anticancer evaluation of the hyperthermic efficacy of anti-human epidermal growth factor receptor-targeted PEG-based nanocarrier containing magnetic nanoparticles

Abstract: Polymeric nanoparticles with targeting moieties containing magnetic nanoparticles as theranostic agents have considerable potential for the treatment of cancer. Here we report the chemical synthesis and characterization of a poly(D,L-lactide- co -glycolide)- b -poly(ethylene glycol)-based nanocarrier containing iron oxide nanoparticles and human epithelial growth factor receptor on the outer shell. The nanocarrier was also radiolabeled with 99m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In the case of IV administration of MNPs, a general dilution effect of the blood and the tumor volume should be considered as well as the limited injection volume. Additionally, the majority of the MNPs tends to accumulate in organs such as the spleen or the liver [79], and only a small fraction of the injected material will accumulate in the tumor, which may limit MHT efficiency [80]. Xie et al confirmed that one single IV injection dose of MNPs does not result in accumulation of enough magnetic material to produce tumor heating [81].…”
Section: Administration Routementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of IV administration of MNPs, a general dilution effect of the blood and the tumor volume should be considered as well as the limited injection volume. Additionally, the majority of the MNPs tends to accumulate in organs such as the spleen or the liver [79], and only a small fraction of the injected material will accumulate in the tumor, which may limit MHT efficiency [80]. Xie et al confirmed that one single IV injection dose of MNPs does not result in accumulation of enough magnetic material to produce tumor heating [81].…”
Section: Administration Routementioning
confidence: 99%
“…In in vitro studies, the sample's temperature is usually measured using an optical fiber submerged in the cell culture medium. Infrared thermal imaging cameras are also used both in vivo and in vitro [80,83,93,94], which displaying a color-code image that correlates with the temperature reached in a specific area. Less conventional, and still under development, techniques include, for example, the use of fluorescence anisotropy-based thermoprobes, which are bioconjugates of dyes and proteins with increased thermo-sensitivity comparatively to the individual molecules [95].…”
Section: Reached Temperature and Time Of Exposurementioning
confidence: 99%
“…Current studies have investigated the excellent hyperthermia performance of MNPs when internalized into tumour cells [10]. Also, types of core-shell iron oxide nanoparticles (IONP) have been designed to enhance the target to organelles of tumour cells, which can improve hyperthermia performance [11,12]. Bi-functional even multi-functional nanoparticles (NPs) have been designed to trigger tumour cells to apoptosis or necrosis by alternating magnetic fields or lasers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…30 Although therapeutic applications of radiolabeled IONP is not the main focus of this article, reports on engineering of these nanoparticles for combined magnetic hyperthermia (or radiation therapy) have shown their potential as novel theranostic nanoagents for both multimodality imaging and therapy. [31][32][33]…”
Section: M Tc-labeled Ionpsmentioning
confidence: 99%